DNA Methylation: A Timeline of Methods and Applications - Parle-Mcdermott, Anne; Harrison, Alan (Frontiers in Genetics, 2011)
DNA methylation is a biochemical process where a DNA base, usually cytosine, is enzymatically methylated at the 5-carbon position. An epigenetic modification associated with gene regulation, DNA methylation is of paramount importance regarding biological health and disease. Recently, the quest to unravel the Human Epigenome commenced, calling for a modernisation of previous DNA methylation profiling techniques. Here, we describe the major developments in the methodologies used over the past three decades to examine the elusive epigenome (or methylome). The earliest techniques were based on the separation of methylated and unmethylated cytosines via chromatography. The following years would see molecular techniques being employed to indirectly examine DNA methylation levels at both a genome-wide and locus-specific context, notably immunoprecipitation via anti-5’methylcytosine and selective digestion with methylation-sensitive restriction endonucleases. With the advent of sodium bisulphite treatment of DNA, a deamination reaction that converts cytosine to uracil only when unmethylated, the epigenetic modification can be identified in the same manner as a DNA base-pair change. More recently, these three techniques have been applied to more technically advanced systems such as DNA microarrays and next generation sequencing platforms, bringing us closer to unveiling a complete human epigenetic profile. While the more recent methods are currently being employed, even newer sequencing platforms and methodologies are being developed to improve our detection of DNA methylation including 5-hydroxymethylcytosine. The next decade is likely to experience an explosion in the number of completed human methylomes or epigenomes; the challenge will be to work out their functional significance.